PENERAPAN PEMBELAJARAN ENVIRONMENTAL LEARNING UNTUK MENINGKATKAN KESADARAN SISWA MENJAGA KEBERSIHAN LINGKUNGAN KELAS DALAM PELAJARAN IPS - Sarah, Siti (2015)
This research was purposed for examining the implementation of environmental learning model in social studies teaching and learning as an stimulation to improve student's environmental awareness for keeping the clenliness of the class. This classroom action research was using mix-methode design with qualitative approach which means that the researcher the became the main instrument, and using a simple quantitative calculation that supports data processing balancely. The subject of this research is students of Eighth grade-1 SMP Negeri 1 Bandung. Instruments of thus research are; interview guidelines, observation, pre-test and post-test result, and field notes. The result of the research indicates empiricly that the implementation of environmental learning improve student's environmental awareness for keeping the clenliness of the class in social studies teaching and learning.